Organization of Hajj of USSR Muslims in the First Half of 1960s - V. A. Akhmadullin (Научный диалог)
The article is devoted to an important aspect of the policy of the Soviet state towards the citizens of the USSR who professed Islam - the organization of trips to the Hajj in the first half of the 1960s. The relevance of the topic is determined by the fact that the share of the Muslim population of Russia is steadily growing both due to the birth rate and due to the entry of a large number of migrants into Russian citizenship, many of whom profess Islam. On the basis of the archive material introduced for the first time, the content of the activities of the Council for Religious Affairs under the Council of Ministers of the USSR, which was the most public body of the Soviet state for interaction with the spiritual departments of Muslims in matters of internal and foreign policy tasks, is considered, which determines the novelty of the study. The author shows the strengths and weaknesses of the methods of work of the party-state apparatus of the Soviet state on the selection of candidates for the Hajj and their admission to the Kingdom of Saudi Arabia. Based on the analysis of the documents, a reasonable conclusion was made that in the USSR the Hajj was organized not to meet the needs of Muslims, but to form a positive image of the USSR in the eyes of Muslims around the world and to increase the authority of the Soviet state among its citizens.